2015
DOI: 10.2172/1182713
|View full text |Cite
|
Sign up to set email alerts
|

Ion Chromatography (IC) Analysis of Glycolate in Simulated Waste

Abstract: The Defense Waste Processing Facility (DWPF) is evaluating the use of glycolic acid as a mercury reductant instead of formic acid during the processing of radioactive waste in the chemical processing cell (CPC). Glycolic acid has been shown to possess improved handling and processing properties when compared to formic acid. An improved method of analysis for glycolic acid by ion chromatography (IC) was developed in support of the alternative reductant flowsheet and applied to simulated Slurry Reciept and Adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 4 publications
0
19
0
1
Order By: Relevance
“… Testing with actual waste confirmed that the Caustic Quench method previously developed [7] should be used for anion measurement by IC for SRAT and SME product slurries and SRAT receipt slurry. 2 No No No No No No No No No No…”
Section: Recommendationsmentioning
confidence: 81%
See 3 more Smart Citations
“… Testing with actual waste confirmed that the Caustic Quench method previously developed [7] should be used for anion measurement by IC for SRAT and SME product slurries and SRAT receipt slurry. 2 No No No No No No No No No No…”
Section: Recommendationsmentioning
confidence: 81%
“…The CQ method was developed as an IC preparation for acidic slurries to stop oxidation reactions, to free up chelated organic acids by converting chelated metal compounds to metal oxides, and to adjust the pH of the sample to match the IC eluent. The CQ preparation and analysis were performed as described in the test report [7]. In the CQ method, ~2 g of 50 wt% NaOH solution was mixed with ~10 g of slurry followed by dilution of a 1 mL aliquot of the CQ mixture to 100 mL with de-ionized water and filtration of the diluted mixtures.…”
Section: Anions In the Slurrymentioning
confidence: 99%
See 2 more Smart Citations
“…• Testing with actual waste confirmed that the Caustic Quench method previously developed [7] should be used for anion measurement by IC for SRAT and SME product slurries and SRAT receipt slurry. 6 No No No No No No No No No No .07 No No No No No No No No No No No 9 1 No No No No No No No No No No No .022 No No No No No No No No No No No 2 No No No No No No No No No No .08 No No No No No No No No No No No 12 14 No No No No No No No No No No No .08 No No No No No No No No No No No .035 No No No No No No No No No No No .045 No No No No No No No No No No No 2 No No No No No No No No No No 5 5 No No No No No No No No No No No 2 No No No No No No No No No No No 22 No No No No No No No No No No No .025 No No No No No No No No No No 7 No No No No No No No No No No No 5 3 No No No No No No No No No No .03 No No No No No No No No No No No…”
Section: Recommendationsunclassified